Prognostic factors and treatment effect of standard-volume plasma exchange for acute and acute-on-chronic liver failure: A single-center retrospective study. Issue 4 (August 2018) - Cheng, Ya-Lien; Chang, Chih-Hsiang; Chen, Wei-Ting; Tsai, Ming-Hung; Lee, Wei-Chen; Tu, Kun-Hua; Tian, Ya-Chung; Chen, Yung-Chang; Hung, Cheng-Chieh; Fang, Ji-Tseng; Yang, Chih-Wei; Chang, Ming-Yang
Abstract: Patients with acute liver failure (ALF) and acute-on-chronic liver failure (ACLF) have a high risk of mortality. Few studies have reported prognostic factors for patients receiving plasma exchange (PE) for liver support. We conducted a retrospective analysis using data of 55 patients with severe ACLF (n = 45) and ALF (n = 10) who received standard-volume PE (1–1.5 plasma volume) in the ICU. Hepatitis B virus infection accounts for the majority of ACLF (87%) and ALF (50%) patients. PE significantly improved the levels of total bilirubin, prothrombin time and liver enzymes ( P <0.05). Thirteen ACLF patients (29%) and one ALF patient (10%) underwent liver transplantation. Two ALF patients (20%) recovered spontaneously without transplantation. The overall in-hospital survival rates for ACLF and ALF patients were 24% and 30%, and the transplant-free survival rates were 0% and 20%, respectively. For the 14 transplanted patients, the one-year survival rate was 86%. Multivariate analysis showed that pre-PE hemoglobin ( P  = 0.008), post-PE hemoglobin ( P  = 0.039), and post-PE CLIF-C ACLF scores ( P  = 0.061) were independent predictors of survival in ACLF. The post-PE CLIF-C ACLF scores ≥59 were a discriminator predicting the in-hospital mortality (area under the curve = 0.719, P  = 0.030). Cumulative survival rates differed significantly between patients with CLIF-C ACLF scores ≤ 58 and those with CLIF-C ACLF scores ≥ 59 after PE ( P < 0.05). The findings suggest that PE is mainly a bridge for liver transplantation and spontaneous recovery is exceptional even in patients treated with PE. A higher improvement in the post-PE CLIF-C ACLF score is associated with a superior in-hospital survival rate.